Edulogy Education Management Information System in Improving the Quality of Education Services: (Case Study of Kumpeh Daaru Attauhid Islamic Boarding School, Jambi Province) - Abdul Halim; Marwazi Marwazi (International Forum of Researchers and Lecturers, 2025)
This study looks at how the implementation of Edulogy-based Education Management Information System (SIMDIK) can improve educational services in Islamic boarding schools in Indonesia, with a special emphasis on the Daaru Attauhid Kumpeh Islamic Boarding School in Jambi Province. Data were collected through observation, documentation, and interviews using a qualitative descriptive case study methodology. Research shows that educational integration improves the process of planning, organizing, implementing, and evaluating education management. However, issues such as lack of digital literacy among employees and limited information technology infrastructure continue to hinder system optimization. The study provides practical insights for Islamic educational institutions that want to use digital systems to improve their services while maintaining Islamic values.